Necessity of post-operative radiograph after percutaneous pinning of supracondylar humerus fracture - Gautam, Keshav Mani; Shrestha, Suman Kumar; Bhatta, Toya Raj (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Complications after closed reduction percutaneous pinning (CRPP) include loss of reduction, pin site infection and iatrogenic nerve injury. There is little evidence to support an ideal post-operative follow-up protocol, leading to variation based on surgeon’s preference. This study aimed to determine the necessity of frequent radiographs after CRPP for supracondylar humerus fracture in children.Method: This was a prospective study involving 34 patients, who underwent CRPP for displaced supracondylar humerus fracture. Patients were divided into two groups: Group A were followed-up at 4 weeks, while Group B were followed-up at one, two and four weeks. There were 18 patients in group A and 16 patients in group B. All radiographs were evaluated for Baumann’s angle and anterior humeral line (AHL) relation with capitellum of humerus.Result: Fourteen patients in Group A and 13 patients in Group B had some change in Baumann angle, but the changes were less than 6 degrees in both groups. There was no change in anterior humeral line relation with capitellum in either group.Conclusion: This study found that loss of reduction after CRPP for supracondylar humerus fractures was similar in both groups. Therefore, post-operative radiographs after CRPP is not necessary.